Antipsychotics: Neurobiological Bases for a Therapeutic Approach - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2013)
Studies on the pathophysiology of schizophrenia have become an adventure. It started with a simple pathological approach, focusing only on positive symptoms caused by dopaminergic hyperactivity in mesolimbic system and then branched out with contributions of many different components, including many receptors, various intracellular signaling pathways and gene-environment interactions. These new approaches have been useful in treating the negative symptoms and cognitive impairment observed in schizophrenia. Since there is a bulk of information on the mechanisms causing the disease, a proportional increase in the number of possible new treatment options has been proposed.The most challenging approaches in the disease mechanism address the glutamatergic system, neuroinflammation, neuroplasticity and neurotrophic factors, genetic factors and some intracellular signaling pathways. In this review, all of the above listed factors are discussed in detail.
Keywords: Schizophrenia; glutamatergic system; neuroinflammation; neuroplasticity; genetics; GLYCOGEN-SYNTHASE KINASE-3; DENDRITIC-SPINE PATHOLOGY; PREFRONTAL CORTEX; SCHIZOPHRENIA; GLUTAMATE; BRAIN; MORTALITY; MODULATOR; DISC1